Factors Related to Febrile Seizures Among Children at Abdul Moeloek Regional Hospital in Lampung Province - Perdani, Roro Rukmi Windi; Marista, Ardina; Wardani, Dyah Wulan Sumekar Rengganis; Suharmanto, Suharmanto; Soleha, Tri Umiana (Malaysian Journal of Medical Sciences, 2025)
Background: Febrile seizures are a significant neurological condition that affects children between the ages of 6 and 60 months and can lead to long-term neurological outcomes, such as neurological, cognitive, and memory impairments. Despite their high global incidence, contributing factors and regional variations are not fully understood, particularly in Indonesia. Methods: A case?control study was conducted at Abdul Moeloek Regional Hospital in Lampung Province, Indonesia, to identify factors associated with febrile seizures among children under five years of age. A total of 72 children with fevers were selected through consecutive sampling in December 2020. Data on body temperature during seizures, fever duration, gender, age, family history of seizures, and birth weight were collected through structured interviews and medical records. Results: Statistical analyses included Chi-square tests and multivariate logistic regression. The results indicated significant associations between febrile seizures and body temperatures exceeding 39°C (P = 0.047; OR = 4.00), fever duration ?24 hours (P = 0.030; OR = 3.35), male gender (P = 0.010; OR = 4.96), positive family history of seizures (P = 0.001; OR = 7.75), and low birth weight < 2,500 grams (P = 0.017; OR = 3.64). Multivariate analysis confirmed family history of seizures ( ? = 2.285, P = 0.001), male gender (? = 1.954, P = 0.005), and elevated body temperature (? = 1.525, P = 0.045) as independent risk factors. Conclusion: Febrile seizures are significantly associated with a positive family history of seizures, male sex, and elevated body temperature. Awareness of these risk factors may improve early recognition and management, ultimately improving paediatric neurological health